The Influence of Parking Activities on the Quality of City - Ariel Yazid Septianto; Inne Yuwinarsih (Program Studi Arsitektur Fakultas Sains dan Teknik (F-INTEN), 2024)
The city of Bandung is a picture of an increase in population and technological developments that can be seen in the land use of urban areas. The majority of people in Bandung City still use private vehicles to travel daily. With this phenomenon, it is not surprising that there are traffic jams everywhere. This also happens in the parking situation in the city of Bandung. Many strategic areas have quite high parking activity. With high activity, be it parking activities with control or without control, it certainly interferes with the circulation of a city space area. Therefore, it is necessary to have an analysis that aims to find out the quality of urban space that affects the circulation of the area. This study analyzed the level of circulation density influenced by parking and activity support around the Jl. Karapitan area, and the method used in this study was a descriptive research method supported by literature reviews and field surveys. That way, an overview of the circulation density of the Jl. Karapitan area will be obtained. The results of this study are expected to be taken into consideration in determining the quality standards of urban space.